Proxy Users Enable Older People Creative Writing on the Web - Toczyski, Piotr; Kowalski, Jarosław; Biele, Cezary (Frontiers in Sociology, 2019)
This paper presents several state-of-the-art concepts within internet studies and applies them to creative writing of older people on the internet. For more than 10 years two creative Web users aged 80+, assisted by younger proxy users, were involved in preliminary action research. Its aim has been to find patterns of inducing older people creativity and sharing their wisdom with the general internet audience. The effectiveness of conducted action research in transferring wisdom using silver digital content is high. It is demonstrated with (a) qualitative participants’ insights, (b) the quantitative description of statistics of blog visits, and (c) the social significance of the topics covered in the created content. Lasting for more than a decade and located within the space of socio-technological solutions in Central and Eastern Europe, the results deliver pattern for emerging technologies aimed at enhancing older people creativity on the Web. The insights from those two action-based case studies enabled the development of new hypotheses. New directions of further, more advanced research of older users' activity within interdisciplinary studies at the crossroads of public health, sociological theory, gerontology and human-computer interaction studies. New research questions are presented to be explored within the social scientific studies on the next-generation internet. Departing from the established concepts and preliminary research, the authors hypothesize that: (1) in order to optimize non-human technology-based assistants human proxy users should be researched; (2) voice assistant technology could become the main proxy for a production of silver digital content; (3) interactive and intelligent technology will be the substitute for social actors that prevent exclusion and disengagement. The remaining research question refers also to the conditions under which the technology can be a viable substitute for a proxy users.